Numerical analysis of complicated waveguide circuits on the basis of generalized scattering matrices and domain product technique (vol 48, pg 305, 2000) - Chumachenko, VP; Pyankov, VP (IEEE-Inst Electrical Electronics Engineers Inc, 2002)
[No abstract available]